Beta-Blockers in the Management of Hypertension and/or Chronic Kidney Disease - Hirofumi Tomiyama; Akira Yamashina (International Journal of Hypertension)
This minireview provides current summaries of beta-blocker use in the management of hypertension and/or chronic kidney disease. Accumulated evidence suggests that atenolol is not sufficiently effective as a primary tool to treat hypertension. The less-than-adequate effect of beta-blockers in lowering the blood pressure and on vascular protection, and the unfavorable effects of these drugs, as compared to other antihypertensive agents, on the metabolic profile have been pointed out. On the other hand, in patients with chronic kidney disease, renin-angiotensin system blockers are the drugs of first choice for achieving the goal of renal protection. Recent studies have reported that vasodilatory beta-blockers have adequate antihypertensive efficacy and less harmful effects on the metabolic profile, and also exert beneficial effects on endothelial function and renal protection. However, there is still not sufficient evidence on the beneficial effects of the new beta-blockers.